Gamma knife radiosurgery for the treatment of glomus jugulare tumors - (:unkn) unknown (SPRINGER, 2010)
The treatment of glomus jugulare tumors represents a challenge for the neurosurgeon, since they invade major vessels and compress critical cranial nerves, resulting in significant morbidity from tumor resection. Among alternative and complementary treatment options, gamma knife radiosurgery is a less invasive procedure and may provide better protection of vital structures. This study aimed to evaluate the efficacy and long-term outcomes of gamma knife surgery in the treatment of these tumors in a large series with the longest follow-up period compared with previous reports. A total of 18 patients with glomus jugulare tumors that underwent gamma knife radiosurgery (GKS) were included. Eleven patients had a history of previous microsurgical treatment. The mean marginal radiation dose was 15.6 Gy (median 15 Gy, range 13-20 Gy). Patients were followed for a mean period of 52.7 months (median 41.5 months); the effect of gamma knife radiosurgery was evaluated using magnetic resonance (MR) images. Based on the last MR images, tumor control could be achieved in 17 out of 18 patients (94.4%). No complications such as radiation-induced peritumoral edema or radiation necrosis occurred. Neurological follow-up examinations revealed improved clinical status in ten patients (55.6%), stable neurological status in seven (38.9%), and deterioration in one patient (5.5%). At the last visit, 17 out of 18 patients were alive. Our results indicate that stereotactic radiosurgery is an effective and safe treatment modality in the management of glomus jugulare tumors, particularly for residual or previously untreated small tumors.
Keywords: Gamma knife radiosurgery; Stereotactic radiosurgery; Glomus jugulare tumors; Tumor control rate; SKULL-BASE; STEREOTACTIC RADIOSURGERY; SURGICAL RESECTION; RADIATION-THERAPY; TEMPORAL BONE; FOLLOW-UP; SURGERY; MANAGEMENT; PARAGANGLIOMAS; EXPERIENCE